2015
DOI: 10.1007/s40843-015-0089-3
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient and tumor vascular-targeting therapeutic technique with size-expansible gadofullerene nanocrystals

Abstract: It has long been a dream to achieve tumor targeting therapy that can efficiently reduce the toxicity and severe side effects of conventional antitumor chemotherapeutic agents. Taking advantage of the abnormalities of tumor vasculature, we demonstrate here a new powerful tumor vascular-targeting therapeutic technique for solid cancers that applies advanced nanotechnology to cut off the nutrient supply of tumor cells by physically destroying the abnormal tumor blood vessels. Water soluble magnetic Gd@C82 nanocry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 34 publications
2
59
0
Order By: Relevance
“…S3). Accordingly, the tissue pathological analysis in the previous report exhibited that the RF assisted GFNCs displayed negligible damage to the normal tissues, even to the liver tissue with higher accumulation of GFNCs [22].…”
Section: Morphological and Functional Observation Of The Tumor Vasculmentioning
confidence: 83%
See 2 more Smart Citations
“…S3). Accordingly, the tissue pathological analysis in the previous report exhibited that the RF assisted GFNCs displayed negligible damage to the normal tissues, even to the liver tissue with higher accumulation of GFNCs [22].…”
Section: Morphological and Functional Observation Of The Tumor Vasculmentioning
confidence: 83%
“…Recently, we reported a new technique based on the radiofrequency (RF)-assisted gadofullerene nanocrystals (GFNCs) which exhibited high-efficient antitumor activity and low toxicity to normal tissues, and may overcome the big problems of VDAs [22]. Briefly, the gadofullerene based nanomaterials were modified with hydroxyl groups on the surface of carbon cage to form the water soluble GFNCs [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2b). It is well known that nanoparticles with radius less than 100 nm could target passively to solid tumor by the enhanced permeability and retention (EPR) effect [47][48][49]. The Cur-NPs satisfy the above conditions, and therefore have the po- tential for the application in cancer therapy.…”
Section: Preparation and Characterization Of The Nanoformulationsmentioning
confidence: 96%
“…Of them we have special interests on fullerenes and metallofullerenes due to their low toxic [28][29][30] metabolizable properties in vivo [31][32][33], as well as their excellent radical scavenging properties. In fact, fullerenes have been reported to protect cells from both ROS hurt and regulate apoptotic process in different biological model systems [34][35][36][37][38], e.g., Moussa et al [39] recently reported that oral administration of C 60 dissolved in olive oil could reduce the oxidative stress induced by the CCl 4 intoxication and largely prolong the lifespan of test rats to double.…”
Section: Introductionmentioning
confidence: 99%